2014
DOI: 10.1177/1741143213513185
|View full text |Cite
|
Sign up to set email alerts
|

Principal preparedness for leading in demographically changing schools

Abstract: This multi-case study sought to construct meaning using a cultural capital lens in relation to educational leadership preparation programs building the capacities of social justice leaders in demographically changing schools. Data revealed principals’ perceptions about preparation, expectations and general beliefs and assumptions related to leadership for social justice emphasizing contradictions between principals’ equity-oriented rhetoric and their underlying beliefs and assumptions affecting their diverse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
1
42
0
1
Order By: Relevance
“…Consistent with Miller and Martin's (2015) research, our study confirmed the importance of practicing and prospective educational leaders identifying their own biases, assumptions and contributions to inequities. Arar (2013, p. 838) concludes: 'Consciousness-altering perspectives' may be fostered in educational leadership preparation programs through case study applications, and structured student involvement in ongoing social justice work.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with Miller and Martin's (2015) research, our study confirmed the importance of practicing and prospective educational leaders identifying their own biases, assumptions and contributions to inequities. Arar (2013, p. 838) concludes: 'Consciousness-altering perspectives' may be fostered in educational leadership preparation programs through case study applications, and structured student involvement in ongoing social justice work.…”
Section: Discussionsupporting
confidence: 92%
“…Sosyal adalet liderliğine odaklanan önceki çalışmalar büyük oranda vaka çalışmaları, sosyal adalet lideri yetiştirme programlarının içeriği ve etkililiği, sosyal adalet liderliğinin önündeki engellerin keşfedilmesi ve sosyal adalet liderliğinin kavramsal çerçevesinin belirlenmesi ile sınırlıdır (Furman, 2012;Furman ve Gruenewald, 2004;Gewirtz, 1998;Miller ve Martin, 2015). Yerli yazında ise sosyal adaletin okullardaki görünümlerinin nasıl olduğu, az sayıdaki çalışma ile belirlenmeye çalışılmıştır.…”
Section: Introductionunclassified
“…Others have documented similar leadership preparation processes aimed at developing social justice oriented leaders who seek equity and excellence in schools (e.g. Brunner et al 2006;Miller and Martin 2015). Recent syntheses of social justice leadership literature (e.g.…”
Section: Critical Transformative Oriented Approachesmentioning
confidence: 99%